2005
DOI: 10.1007/s00701-005-0696-y
|View full text |Cite
|
Sign up to set email alerts
|

Entrapped spinal nerve roots in a pseudomeningocoele as a complication of previous spinal surgery

Abstract: Pseudomeningocele is a rare but well recognised complication of lumbar surgery (microdiscectomy and laminectomy). Most of the patients tolerate the presence of the cyst well, however some present with back pain and spinal claudication, presumably due to neural compression. We report a case who presented following three operations (microdiscectomy, laminectomy and excision of a pseudomeningocele) with symptoms of spinal claudication and bilateral radicular pain. The cause of her pain was evident only at operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…More recently, O'Connor et al [6] and Kothbauer and Seiler [7] reported similar cases after microdiscectomy and laminectomy, or after multiple surgeries [8], now diagnosed by MRI, and treated surgically. Töppich et al [9] reported after microdiscectomy, a case of extensive pseudomeningocele through which the nerve root herniated into the intersomatic space.…”
Section: Discussionmentioning
confidence: 92%
“…More recently, O'Connor et al [6] and Kothbauer and Seiler [7] reported similar cases after microdiscectomy and laminectomy, or after multiple surgeries [8], now diagnosed by MRI, and treated surgically. Töppich et al [9] reported after microdiscectomy, a case of extensive pseudomeningocele through which the nerve root herniated into the intersomatic space.…”
Section: Discussionmentioning
confidence: 92%
“…Usually the origin of the fluid is obvious, but when unclear, the presence of b-2 transferrin establishes the fluid as spinal fluid (15). The types of spinal interventions that have been associated with pseudomeningoceles range from simple lumbar puncture to complex anterior and posterior operations (2,3,(6)(7)(8)(9)(10)(11)(12). The presence of a pseudomengocele anterior to the spine and causing ureteral obstruction is distinctly rare, and we could find no similar case in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Incidental dural tears do not adversely influence the long-term prognosis if they are properly repaired3-5). In addition to nerve root herniation, unrepaired dural tears can lead to pseudomeningocele formation, persistent CSF leakage, meningitis, or arachnoiditis7,11). Ahn et al1) pointed out that unrecognized dural tears follow complex clinical courses because delayed widening of the dural opening by CSF pressure can cause significant neural entrapment, which cannot easily be detected.…”
Section: Discussionmentioning
confidence: 99%